The effect of simvastatin pretreatment on stress-induced gastric ulcer in rats - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Objectives: This study aimed to elucidate the possible protective effect of simvastatin (SIM) pretreatment on stress-induced gastric ulcer in rats. Materials and Methods: Gastric ulcer was produced in Sprague-Dawley rats (250-300 g) by cold-restraint stress. SIM (10 mg/kg/day; per oral) or saline was administered for 21 days prior to stress. On day-21, a group of animals was treated with the non-selective nitric oxide synthase (NOS) inhibitor L-NAME (50 mg/kg; intraperitoneally) or the non-selective cyclooxygenase (COX) inhibitor indomethacin (Indo; 5 mg/kg; subcutaneously) prior to SIM. The stomachs were examined macroscopically and microscopically and stored for biochemical analyses. Results: The severity of the lesions of the stress group was decreased by SIM, but this was not altered significanty by L-NAME or Indo. Stress increased gastric myeloperoxidase activity comparised to control level (p<0.01); however, SIM did not cause a significant change on this parameter. Stress increased gastric chemiluminescence levels (p<0.001) which were reversed by SIM (p<0.001) and this effect continued in L-NAME-or Indotreated animals. Conclusion: SIM pretreatment of rats with cold-restraint stress provided protection against gastric lesion formation via supression of oxidants derived from sources other than neutrophils without the involvement of NOS and COX systems.
Keywords: Ulcer; Nitric oxide synthase; Cyclooxygenase; Rat; Stress